Edible seaweeds of Northern Luzon, Philippines Market prices, local taste preference, seaweed recipes, and other local uses - Moreland, Pamela S. (1979)
The most expensive algae at the public markets surveyed were Porphyra, Caulerpa and an unidentified alga called "panpanao." These algae brought at least Php1.00/ganta at every market where they were sold. Porphyra was consistently the favorite edible seaweed along the northern Luzon coast, and Caulerpa racemosa was preferred in areas to the south where Porphyra was not available. Seaweed recipes vary little from province to province in northern Luzon. Some of the algae of this area have non-food uses: i.e., Sargassum and Turbinaria, to keep insects away from growing vegetables; Digenea simplex, as an anthelmintic; Porphyra, as a possible aphrodisiac; Hydroclathrus, as a spice; Sargassum, as a fertilizer; and Enteromorpha and Chaetomorpha as food for milkfish in fish culture ponds.